The effect of smell and taste of milk during tube feeding of preterm infants (the Taste trial): a protocol for a randomised controlled trial. Issue 7 (17th July 2019) - Beker, Friederike; Macey, Judith; Liley, Helen; Hughes, Ian; Davis, Peter G; Twitchell, Emily; Jacobs, Susan
Abstract : Introduction: Smell and taste of milk are not generally considered when tube feeding preterm infants. Preterm infants have rapid growth, particularly of the brain, and high caloric needs. Enteral feeding is often poorly tolerated which may lead to growth failure and long-term neurodevelopmental impairment. Smell and taste are strong stimulators of digestion and metabolism. We hypothesise that regular smell and taste during tube feeding will improve weight z-scores of very preterm infants at discharge from hospital. Methods and analysis: Taste is a randomised, unblinded two-centre trial. Infants born at <29 weeks' gestation and/or <1250 g at birth and admitted to a participating neonatal intensive care unit are eligible. Randomisation occurs before infants receive two hourly feeds for 24 hours. Infants are randomised to either smell and taste of milk with each tube feed or tube feeding without the provision of smell and taste. The primary outcome is weight z-score at discharge. Secondary outcomes include: days to full enteral feeds, duration of parenteral nutrition, rate of late-onset sepsis, post menstrual age at removal of nasogastric tube and at discharge from hospital, anthropometric data and neurodevelopmental outcomes at 2 years of corrected age. Ethics and dissemination: Human Research Ethics Committees of Mater Misericordiae (trial reference number: HREC/16/MHS/112) and the Royal Women's Hospital (trial reference number: 17/21) last approved the trial protocol (version 4.2; Date: 18 December 2018) and recruitment commenced in May 2017 and November 2017, respectively. The trial results will be published in a peer-reviewed journal and will be presented at national and international conferences. Trial registration number: ACTRN12617000583347.